2008
DOI: 10.1074/jbc.m800945200
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-dependent Transcriptional Activation in Lung Carcinoma Cells by Farnesol Involves p65/RelA(Ser276) Phosphorylation via the MEK-MSK1 Signaling Pathway

Abstract: In this study, we demonstrate that treatment of human lung adenocarcinoma H460 cells with farnesol induces the expression of a number of immune response and inflammatory genes, including IL-6, CXCL3, IL-1␣, and COX-2. This response was dependent on the activation of the NF-B signaling pathway. Isoprenoids are intermediates of the cholesterol/sterol biosynthetic pathway and are formed from mevalonate, which is synthesized from acetyl-CoA by the rate-limiting enzyme 3-hydroxy-3-methylglutaryl-CoA reductase, a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 51 publications
3
54
0
Order By: Relevance
“…Previous studies identify serine 536 as the major phosphorylation site of p65 in response to LPS treatment (29,30), however, the phosphorylation of p65 at Ser 276 was also been reported by phosphotungstic acid and TNF (31,32). Joo and Jetten (33) showed that the S276A mutation significantly reduced the induction of NF-B transcription activation by farnesol, and that inhibition of MEK1/2 by U0126 or knockdown of MEK1/2 expression greatly diminished the phosphorylation of p65 at Ser276 site (but not that of Ser536), suggesting that phosphorylation of p65 at Ser276 is dependent on the activation of the MEK1/2-ERK1/2 pathway. Our unpublished data indicate that the fMLP stimulate a time-dependent increase in phosphorylation of ERK1/2 in human peripheral blood monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies identify serine 536 as the major phosphorylation site of p65 in response to LPS treatment (29,30), however, the phosphorylation of p65 at Ser 276 was also been reported by phosphotungstic acid and TNF (31,32). Joo and Jetten (33) showed that the S276A mutation significantly reduced the induction of NF-B transcription activation by farnesol, and that inhibition of MEK1/2 by U0126 or knockdown of MEK1/2 expression greatly diminished the phosphorylation of p65 at Ser276 site (but not that of Ser536), suggesting that phosphorylation of p65 at Ser276 is dependent on the activation of the MEK1/2-ERK1/2 pathway. Our unpublished data indicate that the fMLP stimulate a time-dependent increase in phosphorylation of ERK1/2 in human peripheral blood monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation at the same site can be achieved by multiple kinases, often in a cell-specific manner. For instance, Ser-276 of p65 is phosphorylated by protein kinase A (PKA) and MSK1, whereas phosphorylation at Ser-536 is mediated by different IB kinases (37,38). Phosphorylation of both Ser-536 and Ser-276 plays critical roles in regulating p65 activity (27, 36, 38 -41).…”
Section: Discussionmentioning
confidence: 99%
“…S7C). These results suggest that PKA-Cβ1 directly phosphorylates p65, independently of activation of p38, ERK, or their downstream kinase MSK1 (mitogen-and stress-activated kinase 1) that has been shown to phosphorylate p65 (66)(67)(68). To further confirm whether PKA-Cβ directly phosphorylates p65, we performed in vitro kinase assay by using recombinant p65 and PKA-Cβ proteins.…”
Section: (E-h) Beas-2b Cells Were Transfected With Sirna (E and F) Ormentioning
confidence: 99%